PEMIKIRAN TASAWUF IMAM AL-GHAZALI DALAM PENDIDIKAN ISLAM - Rosia, Rina (Fakultas Agama Islam UNDARIS, 2018)
AbstractImam al-Ghazali is very popular among Muslims. Muslims are very rare who do not know this character. A number of books by Imam al-Ghazali became the object of study in various Islamic educational institutions, ranging from pesantren to Islamic universities, both at home and abroad. This research is qualitative research including character research. The purpose of this research is to know the thoughts of Sufism of Imam al-Ghazali about Islamic education. The findings of this research are that Imam al-Ghazali was born in a small village of Ghazalah, Kota Thus Province Khurasan Persi region (Iran) in 450 AH / 1058 AD His features are including Sunni tasawuf based on the doctrine ahlu sunnah wal jama'ah. According to him, repentance is the first thing that must be passed by a salik, in other words, no salik is not through this maqam repentance. This is what is called the takhalli phase. It empties itself of both sins to God and to others who are potentially polluting the heart of a salik. After undergoing takhalli phase, after that, the salik enters tahalli phase, which adorns itself with good morals, not just morals good to man but also to God. Salik must undergo the next maqam-maqam like maqam zuhud, patience, syukr, tawakkal, and ridha to arrive at the phase of tajalli. Some of the main doctrines of Sufism of Imam al-Ghazali, namely tawheed, makhafah, mahabbah, and ma'rifat. From these principal teachings was born the concept of taubah, shabr, zuhud, tawakkal, and ridla.Imam al-Ghazali sangat populer di lingkungan umat Islam. Umat Islam amat jarang yang tidak mengenal tokoh ini. Sejumlah kitab karya Imam al-Ghazali menjadi obyek kajian di berbagai lembaga pendidikan Islam, mulai dari pesantren hingga perguruan tinggi Islam, baik di dalam maupun di luar negeri. Penelitian ini adalah penelitian kualitatif termasuk penelitianÂ tokoh. Tujuan penelitian ini adalah untuk mengetahui pemikiran tasawuf Imam al-Ghazali tentang pendidikan Islam. Temuan penelitian ini adalah Imam al-Ghazali dilahirkan di suatu kampung kecil Ghazalah, Kota Thus Propinsi Khurasan wilayah Persi (Iran) pada tahun 450 H/1058 M. Corak pemikirannya adalah termasuk tasawuf sunni yang berdasarkan doktrin ahlu sunnah wal jamaâ€™ah. Menurutnya, taubat adalah hal pertama yang harus dilalui oleh seorang salik, dengan perkataan lain, tak ada salik yang tak melalui maqam taubat ini. Inilah yang disebut sebagai fase takhalli.Yaitu mengosongkan diri dari dosa-dosa baik kepada Allah maupun kepada sesama yang potensial mengotori hati seorang salik. Selesai menjalani fase takhalli, setelah itu, salik memasuki fase tahalli, yaitu menghiasi diri dengan akhlak yang baik, bukan hanya berakhlak baik kepada manusia melainkan juga kepada Allah. Salik harus menjalani maqam-maqam berikutnya seperti maqam zuhud, sabar, syukr, tawakkal, dan ridha untuk sampai pada fase tajalli. Beberapa doktrin pokok tasawuf Imam al-Ghazali, yaitu tauhid, makhafah, mahabbah, dan maâ€™rifat. Dari ajaran-ajaran pokok ini lahir konsep taubah, shabr, zuhud, tawakkal, dan ridla.